SACCHAROMONOSPORA OCEANI VJDS‑3, A POTENT ACTINOBACTERIAL STRAIN FROM MANGROVE ECOSYSTEM - Indupalli, Mani Deepa; Muvva, Vijayalakshmi; Munaganti, Rajesh Kumar; Mangamuri, Usha Kiranmayi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The aim of the present study was to isolate, identify, and analyze the phylogenetic characteristics of a rare actinobacterial strain VJDS‑3 with antagonistic activities isolated from Mangrove ecosystems of Nizampatnam, Guntur District, Andhra Pradesh, India. Methods: Soil samples collected were pre‑treated with calcium carbonate and used for isolation of potent actinobacterial strain designated as VJDS‑3. Identification of the strain was carried out by studying the micro‑morphological, cultural, biochemical, and physiological methods. The phylogenetic study of the strain was carried out by employing 16S rDNA sequence‑based analysis. The phylogenetic tree was constructed using the Molecular Evolutionary Genetic Analysis software version 6. Results: The potent actinobacterial strain was identified as Saccharomonospora oceani VJDS‑3, and the bioactive metabolites produced by the strain inhibited Gram‑positive bacteria (Bacillus megaterium, Bacillus subtilis), Gram‑negative bacteria (Xanthomonas campestris, Pseudomonas aeruginosa, Proteus vulgaris, and Escherichia coli), and fungi (Aspergillus niger, Botrytis cinerea, Fusarium solani, Fusarium Oxysporum, and Candida albicans). Conclusion: The results of the experiment showed that the crude ethyl acetate extract of S. oceani VJDS‑3 showed significant antimicrobial potential, and hence it can be used for isolation of compounds with pharmaceutical importance. Keywords: Mangrove ecosystems, Phylogenetic study, Saccharomonospora oceani VJDS‑3, Bioactive compounds.